Keeping Balance Between Genetic Stability and Plasticity at the Telomere and Subtelomere of Trypanosoma brucei - Li, Bibo (Frontiers in Cell and Developmental Biology, 2021)
Telomeres, the nucleoprotein complexes at chromosome ends, are well-known for their essential roles in genome integrity and chromosome stability. Yet, telomeres and subtelomeres are frequently less stable than chromosome internal regions. Many subtelomeric genes are important for responding to environmental cues, and subtelomeric instability can facilitate organismal adaptation to extracellular changes, which is a common theme in a number of microbial pathogens. In this review, I will focus on the delicate and important balance between stability and plasticity at telomeres and subtelomeres of a kinetoplastid parasite, Trypanosoma brucei, which causes human African trypanosomiasis and undergoes antigenic variation to evade the host immune response. I will summarize the current understanding about T. brucei telomere protein complex, the telomeric transcript, and telomeric R-loops, focusing on their roles in maintaining telomere and subtelomere stability and integrity. The similarities and differences in functions and underlying mechanisms of T. brucei telomere factors will be compared with those in human and yeast cells.